The Modification of Natural Minerals; Modern Technique and Technologies. MTT'2003 - Godymchuk (Godimchuk) A. Yu. Anna Yuryevna (2003, 2003)
The aim of the present work was to analyze the structural and chemical transformations in natural minerals with an increase in temperature. The natural calcium-magnesia minerals of silicate and carbonate rocks were selected for study. The series of minerals "quartz-wollastonite-marble-diopside-dolomite-tremolite" allows to learn principles of phase composition change and structure from SiO2 (100%) up to CaCO3 (100%). The results of EM have shown, that heat treatment lead to destruction of needle-like structure of tremolite crystals. The dates of DTA also testified as changes in tremolite composite. Endothermic effect at 830 degC and simultaneous decreasing of sample mass to 12% testified as process of calcite disintegration.